How Does Strategic Communication Shape Transdisciplinary Collaboration? A Focus on Definitions, Audience, Expertise, and Ethical Praxis - McGreavy, Bridie; Haynal, Kaitlyn; Smith-Mayo, Jennifer; Reilly-Moman, Jessica; Kinnison, Michael T.; Ranco, Darren; Leslie, Heather M. (Frontiers in Communication, 2022)
Transdisciplinary collaboration offers great potential for meaningfully addressing complex problems related to climate change and social inequities. Communication shapes transdisciplinary collaboration in myriad ways, and interdisciplinary and rhetorical approaches to communication can help identify these influences as well as strategies to transform inequitable communication patterns. In this paper, we share results from an engaged and ethnographic research project focused on strategic communication in a large-scale transdisciplinary collaboration to develop environmental-DNA (eDNA) science for coastal resilience. In this context, definitions of eDNA, perspectives about communication, and constructions of audience and expertise shape the ways in which collaborators co-produce knowledge across disciplines and with diverse partners. Identifying relationships among strategic communication, knowledge co-production, and power enables the development of strategic collaborative practices, including asking questions as a means to identify and negotiate differences in definitions of eDNA and using participatory methods and anti-oppressive data management platforms for ethical praxis.